ALASAN PENGUNJUNG BERDARMAWISATA KE KAWASAN PANTAI CAROCOK DI NAGARI PAINAN KECAMATAN IV JURAI KABUPATEN PESISIR SELATAN - ZIKRA, ERIYUS - (Pendidikan Sosiologi, 2014)
Eriyus Zikra (09070294) The Reasons Visitors Visited Carocok Beach In Nagari Painan, Sub-District IV Jurai, Pesisir Selatan Regency. Thesis, Sociology of Education Program STKIP PGRI West Sumatra, Padang. 2014.Tourist Sites is the most preferred place for holiday. From the whole tourist sites in Pesisir Selatan, Corocok Beach is the most visited attractions by foreign and local tourists. This thesis purposed to describe the reasons why the visitors visited Carocok Beach in Nagari Painan, sub-district IV Jurai, Pesisir Selatan Regency. A research method in this research used descriptive qualitative research method. The study site is Nagari Painan, sub-district IV Jurai, Pesisir Selatan Regency. The informants of this research about 15 persons whose visited Carocok Beach according to observation technical studies, interviews and study document. Data accuration analyzed by interactive method consist to data collection, data reduction, data presentation and conclusion. The using theory is fenomenology theory of Alfred Schutz. The result fo research indicated that: (1) the reasons to visiting Carocok Beach is (a) about a beauty charm of Carocok Beach included marine tourism, nature tourism and historical tourism (b) a facility to the Carocok Beach, tourists facilities, Mushalla, parking area and restaurant (c) a hygiene of Carocok Beach either beach and sea (d) security of Carocok Beach secured by Affiliation Agency and Pamong Praja Police Squad (Satpol PP). Thepurposed of visitor to visited is (a) about eliminated stress of life problems (b) enjoying a beauty of Carocok Beach.